Effect of Manganese Chloride in Histological Testes of Male Albino Mice (Baghdad Science Journal, 2011)
The present study was conducted to determine the effect of Manganese on Histopathological changes in testes. Manganese Chloride was given to white mice with oral containing 150_200 and 250 mg/kg for periods of 15_30 and 45 days. The present study recorded the existence of histopathological symptoms in the testes, such as degeneration and necrosis in the tubules, congestion inside blood vessels and Edema in the interstitial tissue, as well as the appearance of giant cells inside the seminiferous tubules.